Pengaruh Simpanan dan Pembiayaan terhadap Peningkatan Pendapatan Anggota Koperasi Konsumen Mitra Manindo Syariah Kayu Jati - Doriana Siregar; Erpiana Siregar; Siti Kholijah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the effect of savings and financing on increasing the income of Mitra Manindo Syariah Kayu Jati Consumer Cooperative members' income. The sample for this research was members of the Mitra Manindo Syariah Kayu Jati Consumer Cooperative, totaling 155 respondents. The dependent variable (Y) in this research is income, the independent variables savings (X1) and financing (X2). The data used is primary data obtained from respondents through the questionnaire provided. The tool used in this research is SPSS version 21. The research results are based on SPSS calculations that savings do not have a significant effect on income. This is proven by the calculated tvalue being smaller than the ttable, namely: (1.827 < 1.976) with a significant value of 0.070 > 0.025. Meanwhile, financing has an effect on income as evidenced by the calculated t being greater than the ttable, namely: (1.996 > 1.976) with a significant value of 0.048 > 0.025. Then the research results show that savings and financing have a positive and significant effect on the income of cooperative members. This is proven by the calculated F value of 8.326 which is greater than the F table value of 3.06 with a significant value of 0.000<0.005.